A Model for On-Line Learning Networks in Engineering Education - Bourne, J. R.; Brodersen, A. J.; Campbell, J. O.; Dawant, M. M.; Shiavi, R. G. (Online Learning, 1997)
This paper describes a model for implementing online learning in engineering education. Relationships between traditional learning strategies and network-enabled engineering education are discussed. The model proposed is based on a World Wide Web implementation that includes presentation materials, online conferencing, demonstrations, and interactive capabilities that permit computer-mediated question and answer sessions. An example of a course implemented using these techniques for a first year engineering course is given. Guidance for engineering educators who wish to implement components of the model is provided.